Sistem pakar untuk mendiagnosis Penyakit karsinoma nasofaring menggunakan forward chaining, dan certainty factor: Study kasus : RSUD Anutapura Palu - SINRA, A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Until these days, diagnosing Nasopharyngeal Carcinoma (NPC) is still a problem caused by uncertainty etiology, unspecific early symptoms, and the hidden position of nasopharynge. On the other hand, Nasopharyngeal Carcinoma also has different symptoms in each patient so that paramedics have difficulties in diagnosing without the help from specialist doctors, especially in Ears, Nose, and Pharynge (THT) as an expert. This research aims to provide an alternative solution to overcome the diagnosing problem in the form of an expert system capable of helping paramedics obtaining early diagnosis of Nasopharyngeal Carcinoma stadium based on symptoms of the patients. Knowledge of the system is production rules provided by THT specialist doctor. The expert systems applies Forward Chaining systematics, and Certainty Factors as uncertainty management. The input from the expert in the form of Nasopharyngeal Carcinoma stadium and its therapy and its supporting symptoms their affect level to the stadium, and also the level of belief of the doctore to the rules. While the input from paramedics is symptoms of patients along with their level of beliefs every symptom in terms of Measure of Belief and Measure of Disbelief to obtain Certainty Factor. Output for the paramedics is the Nasopharyngeal Carcinoma stadium and its therapy as well as the truth level obtained from the inference engine. Keywords— diagnosing NPC stadiums, expert systems, Forward Chaining, Certainty Factors